A contribution to the knowledge of the eriophyoid mites (Trombidiformes: Eriophyidae) associated to Lythraceae with description of a new species from Iran - Sadegh Tajaddod; Parisa Lotfollahi; Enrico de Lillo (Persian Journal of Acarology)
A new eriophyid species (Trombidiformes: Eriophyidae), Aceria salicariae Lotfollahi & Tajaddod sp. nov., from the Ajabshir region in southeastern East Azerbaijan Province in Iran, is described and illustrated. A key to all known eriophyoid species collected on the plants of family Lythraceae is presented. Information about their type hosts, type localities and relation to the host plant as well as remarks about available descriptions of these species are provided.